MO138ASSOCIATION OF NT-PROBNP WITH OBESITY IN CKD PATIENTS. (29th May 2021) - Lin, Ting-Yun; Hung, Szu-Chun
Abstract: Background and Aims: Obesity is associated with lower circulating levels of N-terminal pro-BNP (NT-proBNP) both in the general population and in patients with heart failure. In asymptomatic patients with CKD, NT-proBNP levels are generally elevated. The prevalence of obesity is markedly increasing among patients with CKD. However, whether obesity affects NT-proBNP levels and thresholds for increased risk of clinical outcomes is unclear. Method: We examined the associations between NT-proBNP and obesity in 408 stage 3–5 CKD patients (268 men and 140 women; mean age 65±13 years) free of heart failure at baseline, who were categorized into 3 groups according to body mass index (BMI; kg/m 2 ) as normal (<24.0), overweight (24.0–27.9), and obese (≥28.0). Multivariate Cox proportional hazards models were used to compare the risk associations of NT-proBNP with the composite of ESKD (needing chronic dialysis or kidney transplantation) or all-cause mortality across BMI categories. Results: NT-proBNP levels were significantly lower in obese patients than in normal weight and overweight subjects ( P <0.001). Within each CKD stage, NT-proBNP levels decreased with increasing BMI. In a multivariate analysis, NT-proBNP was inversely associated with obesity, as well as BMI and its fat and lean body mass components (all P <0.001), independent of demographics, comorbidities, and severity of CKD. During a median follow-up of 2.2 years, 117 patients progressed to ESKD and 46 patients died. Overall, higher NT-proBNP levels were independently associated with ESKD or death (HR, 1.52; 95% CI, 1.22–1.89). Specifically, higher NT-proBNP levels were consistently associated with poor outcomes in all BMI categories ( P for interaction = 0.096). Conclusion: Obese CKD patients have significantly lower NT-proBNP levels. Nevertheless, BMI category did not modify the relationship between NT-proBNP and clinical outcomes. Increased risk may be seen at relatively lower levels of NT-proBNP in obese CKD patients.